Complications following transoral robotic surgery (TORS): A detailed institutional review of complications. (April 2017) - Hay, Ashley; Migliacci, Jocelyn; Karassawa Zanoni, Daniella; Boyle, Jay O.; Singh, Bhuvanesh; Wong, Richard J.; Patel, Snehal G.; Ganly, Ian
Highlights: 122 TORS operations were carried out between June 2010 and August 2015. A major complication occurred in 23 patients (18%). There was a temporal trend in TORS related major complication rate decreasing from 33% in 2010 to 10% in 2015. Odds of complication were 3 times greater in patients over 60 years old (p = 0.017). Odds of complication were also 2.5 times greater when more than 2 subsites were resected (p = 0.022). Abstract: Objectives: To report the complications occurring following TORS and to identify the factors predictive of complications. Methods: Following IRB approval a retrospective analysis of all TORS operations at our institution was performed. Postoperative complications within 45 days were collected and graded with the Clavien-Dindo system. Complications were categorized into groups: all complications, not related to TORS and TORS related. Unadjusted odds ratios were calculated to test association between patients with and without a complication. Results: 122 TORS operations were carried out between June 2010 and August 2015. 77% were male, with a median age of 57. There were 92 primary tumor resections, 10 second head and neck primary resections, 13 salvage procedures and 7 other indications. Surgical resection involved 1, 2 or >3 sub-sites in 36%, 28% and 36% patients, respectively. Overall, there were 107 complications (66 TORS related, 41 non-TORS related) that occurred in 57 patients (47%). A major complication occurred in 23 patients (18%). 19 patients had a TORS related major complication and 6 patients experienced a non-TORS related major complication. There was a temporal trend in TORS related major complication rate decreasing from 33% in 2010 to 10% in 2015. Statistical analysis showed that the odds of having any complication were 3 times greater in patients over 60 years old (p = 0.017), and 2.5 times greater when there were more than 2 subsites resected (p = 0.022). Conclusions: Age over 60 years and a larger extent of resection were the significant factors predictive of major complications.